Implementasi Fuzzy ELECTRE Untuk Penilaian Kerusakan Akibat Bencana Alam - Pinem, Agusta Praba Ristadi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2017)
Indonesia is prone to geology natural disasters, such as the earthquake and tsunami. The research aims to develop decision support system that can be used for assessment of damage caused by natural disaster after disaster. The method used in this system is method of fuzzy Â Â ELECTRE and ECLAC. Fuzzy ELECTRE method used to determine the priority of the affected area, while ECLAC method used to calculate the natural disasters damage. Fuzzy method used in the process of assessing the weight and classification process. Variables used in this research is the sector that were damaged. Integration of fuzzy and ELECTRE methods applied in the prioritization of areas affected by natural disasters. The result of this research is classification of disaster area with rank based on weighting. Output visualized decision-making system in the form of dashboards in the form of mapping the area affected by the disaster. The variable rate of interest was made as a decision maker in the form of mapping that indicates the priority areas most severely affected by natural disasters. The process of calculation, analysis and ranking built in one integrated system. Combination mapping and decision support system produce information to support decision making. Ranking information similar with priority in BNPB documents with 0.96 coefficient Rank Spearman correlation (Ï).